MELIA Needs Assessment Results: Assessing the Evaluability of CGIAR’s 2025-30 Portfolio - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
In preparing to assess the evaluability of CGIAR’s 2025-30 Portfolio, IAES surveyed colleagues of the Portfolio’s 13 Science Programs and Accelerators (SP/A’s) to identify specific needs and concerns towards the development of the Evaluability Assessment (EA) Terms of Reference (ToRs) and support during the Portfolio inception period. The survey was jointly designed and administered with the IAES Evaluation Function and CGIAR’s Project Coordination Unit (PCU), with the intent to support SP/A’s colleagues as they prepared their Inception Reports for submission to the Portfolio Performance Unit (PPU) by 2 June 2025.